If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2z + -6 + -7 = -30 Reorder the terms: -6 + -7 + 2z = -30 Combine like terms: -6 + -7 = -13 -13 + 2z = -30 Solving -13 + 2z = -30 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + 2z = -30 + 13 Combine like terms: -13 + 13 = 0 0 + 2z = -30 + 13 2z = -30 + 13 Combine like terms: -30 + 13 = -17 2z = -17 Divide each side by '2'. z = -8.5 Simplifying z = -8.5
| -28n^2=-96-184n | | -176=7x+5(-3x-16) | | 4x+14=2894 | | -5x+2(-4x+6)=77 | | 8(x+6)-8=40 | | -22=-4 | | 28-8x=x | | 29=-4x-7(-2x-17) | | 4x-18=2862 | | -2x-23=513 | | y=15.47+0.2185x | | 5(2x-7)+24=89 | | 4x(10-6)+8-3= | | 21x^2-5-8x=0 | | 7(2x-3)+3=-22 | | 5x+9.9=4.9+10x | | 3y+5/8=4y+1/8 | | x^3+10x^2+x-30=0 | | 21x-31x+8= | | y=0.2185x+15.47 | | 25m^3-5m^2p^2-5mp+p^3= | | 7m=2m-5(-5) | | 3(x-2)=-5 | | [-91]= | | 12p-1=4p+23 | | 16x^4-11x^3+16x^2= | | 2x+1=253 | | 2n+3+3n=n+11 | | 5.3+2.3=17 | | x+3=123 | | 5m^2+12m+2=0 | | 10(11p-7)+4p=158 |